PENGARUH GOOD CORPORATE GOVERNANCE (GCG), CORPORATE SOCIAL RESPONSIBILITY (CSR), DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Jesselyne Ameris Santoso; Yulia Setyarini (J-MACC, 2025)
The primary source of state funding is taxation. Nonetheless, a lot of businesses continue to evade taxes in an effort to legally reduce their tax liability. Despite the fact that it may negatively affect state income, this technique is regarded as legal. The purpose of this study was to ascertain how tax avoidance in property and real estate businesses listed on the IDX in 2020–2023 was impacted by institutional ownership, the audit committee, the independent board of commissioners, corporate social responsibility (CSR), and capital intensity. Secondary data from 79 real estate and property firms listed on the Indonesian Stock Exchange is used in this study. Purposive sampling was used for the sampling, which produced 42 firms between 2020 and 2023. Using the SPSS version 25 software, multiple linear regression is the data analysis method employed. The study's findings indicate that: 1) Institutional ownership significantly and negatively affects tax avoidance. 2) Audit committee does not have a significant effect on tax avoidance 3) tax avoidance is significantly and negatively impacted by an independent board of commissioners. 4). corporate social responsibility does not have a significant effect on tax avoidance 5) capital intensity does not have a significant effect on tax avoidance..